Cyberbullying di Media Sosial Tiktok terhadap Remaja Sekolah Menengah Pertama - Putri, Yessi Mareta Andari; Azahra, Putri Fitrawati; Sinaga, Ester Marito; Prawitri, Ajeng Linggar (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2023)
Abstract Internet use among adolescents, especially junior high school is very risky. Children of this age often assume that the virtual world they use is the same as the real world. The act of insulting or ridiculing on social media is an act that is often known as cyberbullying. The research approach used in this study was a qualitative approach, in which researchers conducted interviews with informants from junior high school youth. This research method uses the spiral silence theory which aims to find out information about the occurrence of cyberbullying on TikTok, the responses of victims of bullying, and analyzing existing data. Cyberbullying is a form of behavior that is carried out by a person when he feels that he is superior in several ways so that he dares to take hurtful actions both physically and mentally, where the application is usually carried out on TikTok. This action comes from the aggressive attitude or apathy of individuals who feel superior so they consider other individuals weak or inferior. The psychological and emotional impact of cyberbullying can trigger the victim's mental shock. However, cyberbullying has the potential to cause more depressive disorders because this bullying material or information will be stored and spread quickly on the internet and can leave digital footprints, anytime and anywhere. As a good internet user and wise in using social media, you should be able to control yourself to not take actions that harm other people. Comments especially on someone whether intentionally or not because all of that can have fatal consequences in the future. With this, junior high school teenagers still need supervision from parents, in which the role of parents is to keep an eye on all their actions, especially those who are moving into junior high school teenagers. Kata Kunci: Cyberbullying, social media, Junior High School Teenagers, TikTok